IMPLEMENTASI ALGORITMA SIMPLE ADDITIVE WEIGHTING UNTUK PEMILIHAN PEGAWAI TERBAIK PADA PT. HASSANA BOGA SEJAHTERA - Ashadul Ushud, Achmad Aditya (Universitas Budi Luhur, 2022)
There are several ways that a company or organization uses to improve its business. One way is to make employees work harder and can produce satisfying work by the company's vision and mission, the method chosen at PT. Hassana Boga Sejahtera is to give the best employee title every month that can motivate its employees to do their best for the company's progress. This research aims to build a decision-making system application that serves as a recommendation to award the title of the best employee at PT. Hassana Boga Sejahtera. The decision-making system is built using the Simple Additive Weighting method and is web-based using the PHP programming language. The criteria used by PT. Hassana Boga Sejahtera consists of work quality, responsibility, discipline, attitude, and cooperation. The results showed that the decision-making system application makes it easier to determine the candidate for the best employee title at PT. Hassana Boga Sejahtera. The results obtained are the highest-ranking score for the best employee title, alternative A15 with a score of 0.93.